Effect of Computer Technology Adoption on Sales Volume in Selected Supermarkets in Kampala Central Division, Uganda - Rugasira, Jack; Moses, Agaba; Kyabarongo, Benon (International Journal of Current Science Research and Review, 2023)
The study looked at the relationship between sales volume and the deployment of computer technology at a few specific supermarkets in Kampala's central division. The specific goal was to look at how the use of computer technology affected the amount of sales in supermarkets. The research used a cross-sectional approach. Approaches that combined quantitative and qualitative methods were used. Data was collected from a sample of 80 respondents in 20 supermarkets in the central division of Kampala using questionnaires and interviews. Data were analyzed using descriptive, correlational, and regression techniques. The results suggested that adoption of computer technology boosts grocery sales. Conclusion: Adoption of computer technology improves operational efficiency, according to the respondents' responses. However, there were a few areas that needed improvement so that efficiency would actually increase. It was advised that the owners of supermarkets purchase and employ improved accounting software, as well as effective monitoring systems and systems that can identify impending expirations and obsolescence and report them early so that action can be taken to prevent losses from expirations.